Digital Interventions to Improve Health Literacy Among Parents of Children Aged 0 to 12 Years With a Health Condition: Systematic Review - Evalotte Mörelius; Suzanne Robinson; Diana Arabiat; Lisa Whitehead (JMIR Publications, 2021)
BackgroundParental health literacy is associated with child health outcomes. Parents are increasingly turning to the internet to obtain health information. In response, health care providers are using digital interventions to communicate information to assist parents in managing their child's health conditions. Despite the emergence of interventions to improve parental health literacy, to date, no systematic evaluation of the effectiveness of the interventions has been undertaken. ObjectiveThe aim of this review is to examine the effect of digital health interventions on health literacy among parents of children aged 0-12 years with a health condition. This includes evaluating parents' engagement (use and satisfaction) with digital health interventions, the effect of these interventions on parental health knowledge and health behavior, and the subsequent impact on child health outcomes. MethodsThis systematic review was registered a priori on PROSPERO (International Prospective Register of Systematic Reviews) and developed according to the Joanna Briggs Institute methodology for systematic reviews. The databases CINAHL, MEDLINE, and PsycINFO were searched for relevant literature published between January 2010 and April 2021. Studies were included if they were written in English. A total of 2 authors independently assessed the search results and performed a critical appraisal of the studies. ResultsFollowing the review of 1351 abstracts, 31 (2.29%) studies were selected for full-text review. Of the 31 studies, 6 (19%) studies met the inclusion criteria. Of the 6 studies, 1 (17%) was excluded following the critical appraisal, and the 5 (83%) remaining studies were quantitative in design and included digital health interventions using web-based portals to improve parents' health knowledge and health behavior. Owing to heterogeneity in the reported outcomes, meta-analysis was not possible, and the findings were presented in narrative form. Of the 5 studies, satisfaction was measured in 3 (60%) studies, and all the studies reported high satisfaction with the digital intervention. All the studies reported improvement in parental health literacy at postintervention as either increase in disease-specific knowledge or changes in health behavior. Of the 5 studies, only 1 (20%) study included child health outcomes, and this study reported significant improvements related to increased parental health knowledge. ConclusionsIn response to a pandemic such as COVID-19, there is an increased need for evidence-based digital health interventions for families of children living with health conditions. This review has shown the potential of digital health interventions to improve health knowledge and behavior among parents of young children with a health condition. However, few digital health interventions have been developed and evaluated for this population. Future studies with robust research designs are needed and should include the potential benefits of increased parent health literacy for the child. Trial RegistrationPROSPERO International Prospective Register of Systematic Reviews CRD42020192386; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=192386